Into the Light: Sexuality, Erasure and Recollection - Ings, W (Routledge, 2019)
Stories of war are constructions. When filmmakers create narratives based on facts, they often need to verify technical details and seek out visual and social contexts for events and the characters who experience them. This article uses a case study of the award-winning short film Sparrow to consider how obscurification and erasure operate both institutionally and socially to render gay soldiers’ experiences of war invisible. Using the true story of an incident that occurred in the Second World War, the article considers the manner in which the impacts and dynamics of shame, the selective nature of ANZAC memorializing, official record keeping, military policy and national legislation can collectively function to distort or render irretrievable the contributions of New Zealand gay men who have served in the nation’s armed forces.
Keywords: Sparrow; Desertion; Homosexuality; Military; Obscurification; Shell shock; Short film; ANZAC